Super-crystals in composite ferroelectrics - D. Pierangeli (Nature Portfolio, 2016)
Crystalline materials are formed by the periodic order of atomic unit cells. Here, Pierangeli et al. report the formation of a ferrelectric super-crystal with micrometric unit cell from modulated nanoscale disorder in potassium-lithium-tantalate-niobate, which is potentially useful for engineering ordered states out of disorder.